2014
DOI: 10.3390/antiox3020245
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Therapy in Patients with Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a major health problem and a growing recognition exists that efforts to prevent it must be undertaken by both governmental and non-governmental organizations. In this context, the pineal product, melatonin, has a promising significance because of its chronobiotic/cytoprotective properties potentially useful for a number of aspects of AD. One of the features of advancing age is the gradual decrease in circulating melatonin levels. A limited number of therapeutic trials have indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 203 publications
(215 reference statements)
3
49
0
1
Order By: Relevance
“…Therapeutic effects of melatonin in AD have been tested in 14 trials including AD patients and 8 trials including MCI patients (reviewed in Cardinali et al, 2014). Melatonin supplementation slows the progression of cognitive impairment in AD and MCI patients, ameliorates sundowning and improves sleep (reviewed in Cardinali et al, 2010).…”
Section: Monoaminergic Systems In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic effects of melatonin in AD have been tested in 14 trials including AD patients and 8 trials including MCI patients (reviewed in Cardinali et al, 2014). Melatonin supplementation slows the progression of cognitive impairment in AD and MCI patients, ameliorates sundowning and improves sleep (reviewed in Cardinali et al, 2010).…”
Section: Monoaminergic Systems In Admentioning
confidence: 99%
“…A search of ClinicalTrials.gov on 15 th February 2016 yielded two studies that tested the effect of melatonin on cognitive functions in MCI patients (phase II) and sleep disturbance associated with AD (phase III). However, some clinical trials in AD patients showed no effects of melatonin on sleep disturbance and agitation (Serfaty et al, 2002; Gehram et al, 2009), suggesting that its efficacy in AD should be further investigated possibly at higher doses (Cardinali et al, 2014). The focus of recent studies is the development of melatonin analogs that could prolong the effect of melatonin.…”
Section: Monoaminergic Systems In Admentioning
confidence: 99%
“…175 Thus, there is increasing interest in potential benefits of melatonin in AD. 176,177 Hypoxia exposure of Wistar rats steadily increased plasma melatonin activity to a plateau at seven days. 178 To what extent the beneficial actions of IHT in AD are due to increased release of melatonin by the pineal gland remains to be determined.…”
mentioning
confidence: 99%
“…[127]). For these effects to occur, doses of melatonin about one order of magnitude higher than those required to affect sleep and circadian rhythmicity are needed.…”
Section: Melatonin and Bzd Use In Insomnia Disorder Patientsmentioning
confidence: 93%